2022
DOI: 10.3389/fimmu.2022.911631
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization analysis reveals causal effects of food intakes on inflammatory bowel disease risk

Abstract: Traditional observational studies have indicated a link between specific food intakes and inflammatory bowel disease (IBD), but the nature of such links remains unknown. We sought to assess the potential causal relationship between food intakes and IBD risk using Mendelian randomization methods. This study used summary statistics data from large-scale genome-wide association studies (GWAS) on food intakes, Crohn’s disease (CD), and ulcerative colitis (UC). In the primary analysis, we used the inverse variance-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Furthermore, a one-sample MR study revealed causal association between asthma onset in childhood and reduced IBD risk in adults, which have less statistical power compared to the two-sample approach [31]. Similarly, investigations into food intakes encountered limitations stemming from sample size issues [32]. In our study, we endeavored to mitigate the aforementioned limitations through speci c approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a one-sample MR study revealed causal association between asthma onset in childhood and reduced IBD risk in adults, which have less statistical power compared to the two-sample approach [31]. Similarly, investigations into food intakes encountered limitations stemming from sample size issues [32]. In our study, we endeavored to mitigate the aforementioned limitations through speci c approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Following the procedure of Chen et al [16], for this study, we selected eligible genetic instrumental variables as follows: (1) the SNPs associated with each exposure (AgeSmk, SmkInit, CigDay, LifSmk and DrnkWk) reached a genome-wide significance threshold (P \ 5 9 10 -8 );…”
Section: Selection Of Genetic Instrumentsmentioning
confidence: 99%
“…However, these observations may have been confounded by unidentified factors, and the causality of the associations was not supported 15 . Randomized controlled trials (RCTs) are the gold standard to determine a causal relationship 16 , 17 , though they are challenging to implement due to ethical constraints. It is often impossible to link specific nutritional interventions to disease outcomes in long-term RCTs because of the difficulty in selecting appropriate control groups and blinding participants and researchers 18 .…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of how different types of foods affect the risk of NMOSD may help develop more effective prediction, treatment, and prevention strategies. The purpose of this study was to assess the causal relationship between dietary patterns and NMOSD using the MR method 16 .…”
Section: Introductionmentioning
confidence: 99%